Can we playfully measure cognitive ability? Construct-related validity and applicant reactions - Marie L. Ohlms; Klaus G. Melchers; Uwe P. Kanning (International Journal of Selection and Assessment, 2023)
We developed a game-based assessment (GBA) measuring cognitive ability for use in personnel selection and examined its construct-related validity. Moreover, applicant reactions toward this GBA were compared with a paper-pencil-based ability test. Both assessment tools were designed to measure verbal, numerical, and figural ability. N0.167em=0.167em183 participants completed the GBA, the paper-pencil test, and questions capturing applicant reactions and personality. We found a strong positive correlation of 0.51 between the overall GBA and paper-pencil test scores, showing evidence for its construct-related validity. Applicant reactions toward the GBA were consistently worse compared with the paper-pencil test. Furthermore, males and individuals with more video game experience held more positive perceptions than females and individuals with less video game experience.
Keywords: 650; applicant reactions; cognitive ability; game-based assessment; gamification; personnel selection